Skrining Fitokimia Dan Uji Sun Protection Factor (SPF) Ekstrak Daun Sungkai (Peronema Canescens Jack) Secara In Vitro - La Mardani Putra; Dwi Fitri Yani; Muhammad Faturrizqi; Putri Rahayu; Osyellah Indar Parawansya (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Sungkai leaves have bioactive compounds in the form of triterpenoids, alkaloids, flavonoids, phenolics, steroids and saponins. This compound contains a chromophore group (conjugated single double bond) which is able to absorb ultraviolet light thereby reducing radiation to the skin. The higher the value, the better it is used as a sunscreen. The purpose of this study was to determine the results of the phytochemical test of the ethanol extract of Sungkai leaves (Peronema Canescens Jack) and the Sun Protection Factor (SPF) test of the ethanol extract of Sungkai leaves (Peronema Canescens Jack) in vitro. The SPF values ​​produced at concentrations of 100, 200, 300, 400, and 500 ppm in ethanol extraction were 7.51; 15.93; 27.40; 34.87; and 39.86. Sungkai Leaf Extract (Peronena Cenescens Jack) can be used as a sunscreen ingredient, at concentrations of 200 ppm, 300 ppm, 400 ppm it is included in the suntan category (moderate to ultra protection) and in this SPF test the concentration will affect the resulting SPF value.